Non‐invasive liver fibrosis assessment correlates with collagen and elastic fiber quantity in patients with hepatitis C virus infection. Issue 1 (26th December 2018) - Yasui, Yutaka; Abe, Tokiya; Kurosaki, Masayuki; Matsunaga, Kotaro; Higuchi, Mayu; Tamaki, Nobuharu; Watakabe, Keiya; Okada, Mao; Wang, Wan; Shimizu, Takao; Takaura, Kenta; Masugi, Yohei; et al.
Abstract : Aim: Elastic fiber deposition is a cause of irreversibility of liver fibrosis. However, to date, its relevance to clinical features has not yet been clarified. This study aimed to clarify the correlation between non‐invasive markers of fibrosis and fiber quantity, including elastic fiber, obtained from computational analysis. Methods: This retrospective study included 270 patients evaluated by non‐invasive liver fibrosis assessment prior to liver biopsy. Of these patients, 95 underwent magnetic resonance elastography (MRE) and 244 were assessed with Wisteria floribunda agglutinin‐positive Mac‐2 binding protein (WFA + ‐M2BP). Using whole‐slide imaging of Elastica van Gieson‐stained liver biopsy sections, the quantity of collagen, elastin, and total fiber (elastin + collagen) was determined. Results: The total fiber quantity showed significant linear correlation with fibrosis stage F0–F4. Collagen fiber quantity increased from stage F0 to F4, whereas elastic fiber quantity increased significantly only from stage F2 to F3. Spearman's rank correlation test revealed that non‐invasive liver fibrosis assessment significantly correlates with each fiber quantity, including correlation between total fiber quantity and the Fibrosis‐4 (FIB‐4) index ( r = 0.361, P < 0.001), WFA + ‐M2BP values ( r = 0.404, P < 0.001), and liver stiffness value by MRE ( r = 0.615, P < 0.001). Receiver operating characteristic (ROC) curve analyses revealed that the area under ROC for predicting higher elastic fiber (>3.6%) is 0.731 by FIB‐4 index, 0.716 by WFA + ‐M2BP, and 0.822 by liver stiffness by MRE. Conclusion: Liver fibrosis correlates with fiber quantity through non‐invasive assessment regardless of fiber type, including elastic fiber. Moreover, MRE is useful for predicting high amounts of elastic fiber.